Expression of the Aspergillus bimG gene in Neurospora crassa - B Csóka; T Kókai Zeke; J Doonan; H Fox; Z Fehér; V Dombrádi (Fungal Genetics Reports, 2002)
In A. nidulans the bimG gene codes for the catalytic subunit of protein phosphatase 1. The wild type bimG gene was transformed into N. crassa and expressed under the direction of the alcA promoter. The heterologous bimG mRNA and protein were detected in the transformants by RT-PCR and Western blotting, respectively. However, the transformation did not result in detectable changes in phenotype. This work demonstrates that the alcA promoter, a conditional gene expression system widely used in both Aspergillus and higher plants, also functions in N. crassa.